Assessing the Impact of High-Quality Economic Development on Carbon Productivity in China - Lingdi, Li (Universiti Malaysia Sarawak, 2025)
Under China’s “dual carbon” strategy, enhancing carbon productivity has emerged as a crucial pathway for advancing green economic transformation and aligning high-quality development with carbon neutrality. As an indicator of economic output per unit of carbon emissions, carbon productivity is a measure of both ecological and economic value. While pursuing high-quality growth, China faces complex challenges, including growing resource and environmental constraints, industrial restructuring pressures, and significant regional disparities. With its commitment to peak carbon emissions by 2030 and achieve carbon neutrality by 2060, China must operate within a narrow timeframe to fulfill its international responsibilities as a global economic power.This study investigates carbon productivity in 30 provincial-level regions in China from 2008 to 2021 using an integrated analytical framework grounded in theories of sustainable development, low-carbon economy and decoupling theory, and spatial econometrics theories. It constructs a multidimensional index system to assess the influence of high-quality development on carbon productivity across static, dynamic, and spatial dimensions. Empirical analysis using static panel models, the system of Generalized Method of Moments, and the Spatial Durbin Model reveals that while carbon productivity in China has generally increased, regional disparities persist; most notably, there is a pattern of higher productivity in eastern regions as compared to western regions. High-quality economic development yields a significant positive impact on carbon productivity, particularly over the long term, indicating strong path dependence and structural reinforcement. Furthermore, spatial spillover effects are evident, whereby advancements in high-quality development within one region also improve the carbon productivity of neighboring areas. Additionally, factors such as energy intensity, urbanization, government environmental investment, and marketization exhibit diverse influences on carbon productivity across regions.Drawing from these findings, the study proposes targeted policy recommendations, including deepening the high-quality development agenda, promoting green industrial transformation, optimizing the energy structure, strengthening cross-regional coordination, and enhancing fiscal environment supports. It also underscores the strategic role of the stateowned sector in driving green transition, advocating for a “Chinese path” to low-carbon development—one that avoids the conventional Western trajectory of “pollute first, control later” and instead aligns with China’s developmental stage and governance framework.